2012
DOI: 10.4161/cc.11.4.19097
|View full text |Cite
|
Sign up to set email alerts
|

New insights into replication origin characteristics in metazoans

Abstract: We recently reported the identification and characterization of DNA replication origins (Oris) in metazoan cell lines. Here, we describe additional bioinformatic analyses showing that the previously identified GC-rich sequence elements form origin G-rich repeated elements (OGREs) that are present in 67% to 90% of the DNA replication origins from Drosophila to human cells, respectively. Our analyses also show that initiation of DNA synthesis takes place precisely at 160 bp (Drosophila) and 280 bp (mouse) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
145
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(175 citation statements)
references
References 47 publications
29
145
0
1
Order By: Relevance
“…Nevertheless, it is intriguing that the sequence-specificity of RNA/ssDNA binding of human ORC coincides with a common signature of human replication origins (i.e. G4-preferable sequences) (14,15,30). Human ORC does not exhibit the preference to G-rich dsDNA as shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, it is intriguing that the sequence-specificity of RNA/ssDNA binding of human ORC coincides with a common signature of human replication origins (i.e. G4-preferable sequences) (14,15,30). Human ORC does not exhibit the preference to G-rich dsDNA as shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Although the previous studies suggest that ORC recruitment to the origin sites involves several factors including sequences such as CpG islands, chromatin structure, histone modification, DNA-binding proteins such as transcription factors, or transcription itself (1,2), the details of the mechanism of ORC recruitment to the specified origin sites are still elusive. The recent genome-wide mapping of replication origins revealed that a G-rich repeat element was present in most of the replication origins in mouse and human cells (14,15). This G-rich element potentially forms G-quadruplex (G4), but the biological role of this element has not been examined yet.…”
mentioning
confidence: 99%
“…G quadruplexes (G4) have been frequently found in association with TEs (44) and with ORIs in mammalian cells (4,(45)(46)(47). Thus, we also asked whether the presence of G4 was a determinant factor in the distribution of ORIs in Arabidopsis cells.…”
Section: The Activity Of Ori-tes Is Maintained With High Levels Of MCmentioning
confidence: 99%
“…Thus, an attribute shared by most origins studied across the tree of life is the occurrence of AT-rich features. However, recent genome-wide studies have suggested that origins in multicellular eukaryotes may be GCrich and correlated with motifs for G-quadruplex (G4) structures (Cayrou et al 2011(Cayrou et al , 2012Besnard et al 2012;Picard et al 2014). Intrastrand G4 structures are highly stable DNA secondary structures that can form at physiological conditions in vitro when a DNA strand has four or more adjacent poly-G tracts typically defined as being separated by loops of 1-7 nucleotides (nt) (Huppert 2010;Bochman et al 2012).…”
mentioning
confidence: 99%